Issues and Potentials of Research Topics in Medicines:A Research Priority Setting (RPS) in The Indonesian Institute of Sciences (LIPI) - Hadi Kardoyo; Mia Rahma Romadona; Setiowiji Handoyo (STI Policy and Management Journal, 2020)
This article ilustrates the findings of research priority setting (RPS) in the field of medicine and health at the Indonesian Institute of Sciences (LIPI) in 2017. This RPS has been conducted to address issues and explore potential research topics in LIPI in the area of drug and health industry. The RPS stage has been conducted with the Delphi Method and produced five major issues, namely 1). Structure of the pharmaceutical industry in Indonesia, 2). The Role government R&D institutions and universities in the structure of the pharmaceutical industry, 3). Standardization and product supervision, and 5). Policies in the sectoral innovation system. Based on these major issues, LIPI has potential research topics that need to be developed, as follows: 1) Research on "marker" compounds and development of "markers bank ", 2) Research on combinations of chemical compounds in medicinal and health products, 3) Social research related to public acceptance of medicinal products, 4) Research on the potential of herbal medicines originating from "indigenous knowledge ", 5) The need to develop a catalog of potential herbal medicinal ingredients, 6) Development of formulations of finished drug products based on the expired patent utilization, 7) Development of research for phytofarmaceutical products, 8) Development of research on reagents to support research activities in the fields of health and medicine, 9) Development of technological capabilities that is needed to support research activities in the fields of health and medical treatment, 10) Development of research topics by referring to the ministry's pharmaceutical industry development road map and 11) Research potential in R&D institutions and universities with reference to R&D and manufacturing scenario of APIs. The outputs of RPS will be the basis for LIPI to focus on research in the field of medicine and health for the years 2017--2026. Keywords: research priority setting, pharmaceutical industry, medicine research, pharmaceutical industry